ANALISIS SENSORIS PRODUK SUSU PASTEURISASI KOMERSIAL PADA ANAK-ANAK TINGKAT SEKOLAH MENENGAH PERTAMA DI PURWOKERTO DAN BANJARNEGARA - , YUDISTIRA SENA DEWANTORO, Prof. Dr. Ir. Tridjoko Wisnu Murti, DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Most people tend to choose milk that has been processed rather than fresh milk, because it taste better than fresh milk. This study aims to relate the sensory data, instrument data with consumer data and determine acceptance and consumer preference for commercial pasteurized milk products. Fresh milk quality testing include fat content, protein content , lactose content and total solids content. The sensory test includes a sweet taste with a selection of likes and dislikes as well as testing the physical properties of the milk that is odor and viscosity. Panelists are children of secondary school (SMP) who is amounted for 90 children aged 12 to 14 years. Sensory testing and preferential include smell, taste, viscosity and acceptance. The test results obtained quality fresh milk 3.91 % fat , 2.86% protein content , lactose content of 4.25 % and total solids content of 11.61%. The results of sensory tests and preferential analyzed using Chi-square test. An average of results obtained in Banjarnegara for resources received 2.40(A), 2.93(B), 3.27(C), 2.78(D) and 3.31(E). An average results obtained in Purwokerto for resources received: 2.78(A), 3.09(B), 3.07(C), 2.82(D) and 3.18(E). The test results showed that the quality of fresh milk dairy in normal circumstance. The test results showed that the sensory and preferential normal smell, taste sweet (normal) and the received power is the most preferred milk dairy C and E. Conclusions is consumers prefer milk with a sweet taste. Keyword: Pasteurized Milk, Quality Test, Test Sensorial, Children Secondary School